2023
DOI: 10.1112/plms.12543
|View full text |Cite
|
Sign up to set email alerts
|

Associahedra for finite‐type cluster algebras and minimal relations between g‐vectors

Arnau Padrol,
Yann Palu,
Vincent Pilaud
et al.

Abstract: We show that the mesh mutations are the minimal relations among the ‐vectors with respect to any initial seed in any finite‐type cluster algebra. We then use this algebraic result to derive geometric properties of the ‐vector fan: we show that the space of all its polytopal realizations is a simplicial cone, and we then observe that this property implies that all its realizations can be described as the intersection of a high‐dimensional positive orthant with well‐chosen affine spaces. This sheds a new light o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…After the appearance of the first version of this paper in 2018, Palu, Padrol, Pilaud, and Plamondon [26] showed that a very similar construction can be applied to construction of generalized associahedra for all seeds in all Dynkin‐type cluster algebras. The first author of the present paper also extended the techniques in the present paper in her thesis [5], giving another proof that the same construction can be applied to any seed of simply laced Dynkin type, and that this construction also gives Newton polytopes of F$F$‐polynomials in the same generality.…”
Section: Introductionmentioning
confidence: 99%
“…After the appearance of the first version of this paper in 2018, Palu, Padrol, Pilaud, and Plamondon [26] showed that a very similar construction can be applied to construction of generalized associahedra for all seeds in all Dynkin‐type cluster algebras. The first author of the present paper also extended the techniques in the present paper in her thesis [5], giving another proof that the same construction can be applied to any seed of simply laced Dynkin type, and that this construction also gives Newton polytopes of F$F$‐polynomials in the same generality.…”
Section: Introductionmentioning
confidence: 99%
“…The search of irredundant facet descriptions of deformation cones of particular families of combinatorial polytopes has received considerable attention recently [3,7,9,10,12,32,33]. One of the motivations sparking this interest arises from the amplituhedron program to study scattering amplitudes in mathematical physics [6].…”
Section: Introductionmentioning
confidence: 99%
“…One of the motivations sparking this interest arises from the amplituhedron program to study scattering amplitudes in mathematical physics [6]. As described in [33,Sec. 1.4], the deformation cone provides canonical realizations of a polytope (seen as a positive geometry [5]) in the positive region of the kinematic space, akin to those of the associahedron in [4].…”
Section: Introductionmentioning
confidence: 99%